RUSSIAN PRONOUNS: FORMS AND USES OF PERSONAL, POSSESSIVE, INDICATIVE, REFLEXIVE, AND RELATIVE PRONOUNS, AND THEIR CASE FORMS - Dzuraeva Farakhbonu Isamtillo's daughter; Abdukhakimov son of Begzod Sanjarbek; Izzatullayeva Shakhnoza Erkin's daughter; Mahomadiyev Mehroj Marufvich (European Science Publishing, 2024)
This article provides an in-depth overview of Russian pronouns, covering their various forms and functions. It explores five key types of pronouns: personal, possessive, indicative, reflexive, and relative. The article examines how these pronouns change according to gender, number, and case, and provides examples of their usage in sentences. By explaining the different cases (nominative, accusative, genitive, dative, instrumental, and prepositional), the article helps readers understand the structure and grammatical nuances of Russian pronouns. This comprehensive guide is an essential resource for learners aiming to master Russian grammar and sentence construction.
Keywords: Russian grammar, Russian pronouns, Personal pronouns, Possessive pronouns, Reflexive pronouns, Relative pronouns, Indicative pronouns, Russian cases, Noun cases in Russian, Russian language structure.